2021
DOI: 10.3389/fcimb.2020.585917
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Porphyromonas gingivalis Outer Membrane Vesicles in Periodontal Disease and Related Systemic Diseases

Abstract: Periodontal disease is a chronic infectious disease associated with a variety of bacteria, which can cause damage to the periodontal support structure and affect a variety of systemic system diseases such as cancer, cardiovascular disease, diabetes, rheumatoid arthritis, non-alcoholic fatty liver, and Alzheimer’s disease. Porphyromonas gingivalis (P. gingivalis) is the most important pathogenic bacteria for periodontal disease. It can produce outer membrane vesicles (OMVs) and release them into the environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
134
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(143 citation statements)
references
References 105 publications
6
134
0
3
Order By: Relevance
“…Through long-distance transmission, Pg OMVs can reach distant target organs and induce related systemic diseases. A recent review of this subject [142] indicates the correlation between Pg OMVs and systemic system diseases. First, in cardiometabolic diseases, Pg OMVs attenuate insulininduced Akt/GSK-3␤ signaling in hepatic HepG2 cells, thereby causing changes in glucose metabolism in the liver and promoting the development of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Through long-distance transmission, Pg OMVs can reach distant target organs and induce related systemic diseases. A recent review of this subject [142] indicates the correlation between Pg OMVs and systemic system diseases. First, in cardiometabolic diseases, Pg OMVs attenuate insulininduced Akt/GSK-3␤ signaling in hepatic HepG2 cells, thereby causing changes in glucose metabolism in the liver and promoting the development of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Given that NTHi and M. catarrhalis have been shown to release OMVs, that can activate host immune responses as well as potentially support bacterial colonization, they may provide a novel mechanism contributing to the nature of chronic and recurrent bacterial infections in AECOPD and systemic disease. In support of this, a recent review highlighted the role of Porphyromonas gingivalis in promoting the development of related systemic diseases including diabetes and cardiovascular disease through long distance transmission of OMVs (140,141). Further research is, therefore, required to determine role of OMVs in COPD and other systemic diseases.…”
Section: Immune and Inflammatory Role Of Evs In Response To Respiratory Infectionmentioning
confidence: 98%
“…These findings suggest that bacteremia may not be a temporary nor a localized problem. Furthermore, it has been revealed that microbes can be found in the lungs of healthy people [5,85,86] and cancer patients [87], the placenta of healthy pregnant women, albeit controversial [1-4], and the brains in Alzheimer's disease (AD) [88][89][90][91], which had long been considered sterile.…”
Section: Focal Infection Theory and Leaky Gummentioning
confidence: 99%